2022
DOI: 10.5708/ejmh/17.2022.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Parental Burnout in Hungary - Development and Psychometric Evaluation of the Hungarian Parental Burnout Assessment (PBA-HUN)

Abstract: Introduction: Parental burnout might take place when excessive demands overwhelm the parents’ resources. Aims: To develop and validate the Hungarian version of the Parental Burnout Assessment (PBA-HUN), an instrument designed to measure parental burnout; and to determine the prevalence of parental burnout in Hungary. Methods: Data were collected via an online survey from parents with at least one child living in the household (N = 1215; 82.6% mothers; Mage = 38.68 years; SDage = 6.27 years). Confirmatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…First, although the present study was carried out among a relatively large sample, the majority of participants were mothers. Fathers’ participation in parental burnout studies in other countries is also lower than that of mothers ( Roskam et al, 2018 ; Aunola et al, 2020 ; Hamvai et al, 2022 ). However, in our sample, this difference is especially notable.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…First, although the present study was carried out among a relatively large sample, the majority of participants were mothers. Fathers’ participation in parental burnout studies in other countries is also lower than that of mothers ( Roskam et al, 2018 ; Aunola et al, 2020 ; Hamvai et al, 2022 ). However, in our sample, this difference is especially notable.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the prevalence of PB, respondents were considered to experience PB if they scored 92 or higher on the PBA, which is the mean score of a parent who experiences every symptom at least once a week ( Szczygieł et al, 2020 ; Sarrionandia and Aliri, 2021 ; Hamvai et al, 2022 ). Using this cut-off, the prevalence rate of burnout stood at 10.17% in the total sample; 10.83% for mothers and 3.13% for fathers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of burnout increases cynicism, helplessness, depression, hopelessness, and psychologically demanding situations. [5,[18][19][20] The statistical record showed that 3.5 million parents in the US, [17] barely 5% in the European and Anglo-Saxon countries, [21] and above 5% in Hungary [22] experienced burnout. Burnout could be experienced by everyone irrespective of gender male or female.…”
Section: Philosophy Of Divorcementioning
confidence: 99%